Relationship of Marketing Mix, Brand Equity to Purchase Decision and Loyalty with Digital Wallet as Moderating during the Covid 19 Pandemic Period - Setiarini Setiarini; Aulia Keiko Hubbansyah; Iha Haryani Hatta (PT Mattawang Mediatama Solution, 2023)
This study aims to examine the relationship between Marketing Mix, Brand Equity with Purchase Decisions, and Loyalty with Digital Wallets to reinforce the relationship between Brand Equity and purchasing decisions. This research is included in cross-sectional research because it was conducted at a particular time and was not compared with other studies. The sample selection technique used non-probability sampling, namely convenience samples, and questionnaires were distributed via e-link via Whatsapp and Facebook. The sample of this study is the population aged 17 years and over who live in Jakarta, Bogor, Depok, Tangerang, and Bekasi. The number of research samples is 271 respondents. This study uses a simultaneous equation approach model with two-stage least square (2SLS) estimation techniques and data processing with SPSS version 26.00. The results showed that marketing mix, brand equity, and customer loyalty positively and significantly affected customer satisfaction. Digital wallets played a moderating factor, statistically, do not influence purchasing decisions. Purchase decisions and customer satisfaction positively and significantly influence customer loyalty. The findings of this study are that in improving smartphone purchasing decisions, the best effort is to prioritize aspects of the marketing mix and brand equity. The digital wallet is not a factor that drives consumer purchasing decisions. Furthermore, customer loyalty can be built in the long term through efforts to optimize purchasing decisions and customer satisfaction